Application of LDH/Halloysite Nanocomposite as Solid-Phase Microextraction Fiber Adsorbent for Determination of Phenolic and Chlorophenols Compounds - Marzieh Piryaei; Mir Mahdi Abolghasemi; Sona Hassani (Nanochemistry Research)
In this research, layered double hydroxide/halloysite (LDH/Halloysite) nanocomposite was synthesized as a coating for solid-phase microextraction fiber for extraction of phenolic compounds (PCs) in the plasma and water samples. The size, morphology, composition, and properties of the prepared nanocomposite were also characterized using scanning electron microscopy (SEM), Fourier transform- infrared spectroscopy (FT-IR), energy-dispersive X-ray spectrometry (EDX), and thermogravimetric analysis (TGA). After solid-phase microextraction, the phenolic compounds were quantified via gas chromatography-mass spectrometry. Analytical merits of the method, under optimum conditions (extraction temperature: 80°C, extraction time: 30 min, pH: 6.5, stirring rate: 500 rpm, and salt concentration: 15% wv-1), are 0.01–200 ng mL-1 for the linear dynamic range and 0.2-4 pgmL-1 for the limit of detection. In optimum conditions, the repeatabilities for one fiber (n = 3), expressed as relative standard deviation, was between 4.1 and 7.6% for the phenolic compounds. Ultimately, for the analysis of the river water and plasma samples, the SPME technique was successfully applied.